Bilateral Pheochromocytomas in a Patient with Y175C Von Hippel-Lindau Mutation - Olga Astapova; Anindita Biswas; Alessandra DiMauro; Jacob Moalem; Stephen R. Hammes (Case Reports in Endocrinology)
Von Hippel-Lindau (VHL) disease, caused by germline mutations in the VHL gene, is characterized by metachronously occurring tumors including pheochromocytoma, renal cell carcinoma (RCC), and hemangioblastoma. Although VHL disease leads to reduced life expectancy, its diagnosis is often missed and tumor screening guidelines are sparse. VHL protein acts as a tumor suppressor by targeting hypoxia-inducible factors (HIFs) for degradation through an oxygen-dependent mechanism. VHL mutants with more severely reduced HIF degrading function carry a high risk of RCC, while mutants with preserved HIF degrading capacity do not cause RCC but still lead to other tumors. VHL disease is classified into clinical types (1 and 2A-2C) based on this genotype-phenotype relationship. We report a case of bilateral pheochromocytomas and no other VHL-related tumors in a patient with Y175C VHL and show that this mutant preserves the ability to degrade HIF in normal oxygen conditions but, similar to the wild-type VHL protein, loses its ability to degrade HIF under hypoxic conditions. This study adds to the current understanding of the structure-function relationship of VHL mutations, which is important for risk stratification of future tumor development in the patients.